2018
DOI: 10.1513/annalsats.201711-900oc
|View full text |Cite
|
Sign up to set email alerts
|

Traffic-related Air Pollution, Lung Function, and Host Vulnerability. New Insights from the PARIS Birth Cohort

Abstract: This study sheds new light, suggesting associations between postnatal traffic-related air pollution exposure and reduced lung function may be enhanced by early, repeated lower respiratory tract infections or allergic sensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 29 publications
3
21
0
7
Order By: Relevance
“…Lung function tests were carried out at 8‐9 years, as previously described . Spirometry was performed at baseline and 20 minutes after the administration of 200 μg of salbutamol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung function tests were carried out at 8‐9 years, as previously described . Spirometry was performed at baseline and 20 minutes after the administration of 200 μg of salbutamol.…”
Section: Methodsmentioning
confidence: 99%
“…Lung function tests were carried out at 8-9 years, as previously described. 10 Spirometry was performed at baseline and 20 minutes after the administration of 200 μg of salbutamol. Forced expiratory volume in one second (FEV 1 ), forced vital capacity (FVC), and forced expiratory flow at 25%-75% of the FVC (FEF 25%-75% ) were recorded.…”
Section: Lung Functionmentioning
confidence: 99%
“…Different exposure windows during lung development have been investigated in order to identify a critical time frame. While some studies reported small-scale associations between higher air pollution exposure during pregnancy and reduced lung function at school-age (Bougas and Ranciere, 2018;Jedrychowski et al, 2010;Jedrychowski et al, 2015;Morales et al, 2015;Mortimer et al, 2008), other studies reported that exposure during infancy, but not pregnancy, was associated with reduced lung function at school-age (Schultz et al, 2012;Schultz et al, 2016). These conflicting findings suggest that different exposure windows during lung development may differently affect lung function.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse effects of air pollution on lung function in newborns (Latzin et al, 2009), during childhood (Bougas and Ranciere, 2018;Jedrychowski et al, 2010;Jedrychowski et al, 2015;Morales et al, 2015;Mortimer et al, 2008;Schultz et al, 2012) and adolescence (Schultz et al, 2016) have been reported. Different exposure windows during lung development have been investigated in order to identify a critical time frame.…”
Section: Introductionmentioning
confidence: 99%
“…In animal toxicology, prenatal plus early postnatal exposure to PM 2.5 from motor vehicle sources has been found to impair lung growth (8), although little (if any) mechanistic research has focused on vulnerable periods during gestation. On the other hand, identifying an especially sensitive trimester has been of great interest in epidemiologic research, with inconclusive results (1,9,10). This question may be unanswerable with observational data because a trimester lasts 3 months and is therefore a snapshot of pollution exposure that aligns perfectly with season.…”
mentioning
confidence: 99%